Utilization of numerical techniques to predict the thermal behavior of wood column subjected to fire part B: Analysis of column temperature and fire resistance - Elshayeb M.; Malik A.R.A.; Ideris F.; Hari Z.; Razak N.A.; Siang J.E.L.; Anuar Z. (Trans Tech Publications Ltd, 2023)
Mathematical models of Part A [1] are used to calculate the temperatures, deformations and fire resistance of rectangular, hexagonal, octagonal and I-cross section columns for the purpose of Part B. In this paper the comparison among the configurations of the column has been carried out to predict the temperature history for the column elements for preventing the spread of fire and prolonging the structural time collapse. The columns are varied in section size, among them are the rectangular, hexagonal, octagonal and I-cross section column of Keruing timber. The developed mathematical models defined the failure point as the point which the column can no longer support the applied load. From the comparison, the I-cross section column is the worst configuration than the other configuration.